Work organization in hospital wards and nurses' emotional exhaustion: A multi-method study of observation-based assessment and nurses' self-reports. (September 2016) - Stab, Nicole; Hacker, Winfried; Weigl, Matthias
Abstract: Background: Ward organization is a major determinant for nurses' well-being on the job. The majority of previous research on this relationship is based on single source methods, which have been criticized as skewed estimations mainly due to subjectivity of the ratings and due to common source bias. Objectives: To investigate the association of ward organization characteristics and nurses' exhaustion by combining observation-based assessments with nurses' self-reports. Design and participants: Cross-sectional study on 25 wards of four hospitals and 245 nurses. Setting: Our multi-method approach to evaluate hospital ward organization consisted of on-site observations with a standardized assessment tool and of questionnaires to evaluate nurses' self-reports and exhaustion. Methods: After establishing the reliability of our measures, we applied multi-level regression analyses to determine associations between determinant and outcome variables. Results: We found substantial convergence in ward organization between the observation-based assessments and nurses' self-reports, which supports the validity of our external assessments. Furthermore, two observation-based characteristics, namely participation and patient-focused care, were significantly associated with lower emotional exhaustion among the nurses. Conclusions: Our results suggest that observation-based assessments are a valid and feasible way to assess ward organization in hospitals. Nurses' self-reported as well as observation-based ratings on ward organization were associated with nurses' emotional exhaustion. This is of interest mainly for identifying alternative measures in evaluating nurses' work environments, to inform health promotion activities and to evaluate job redesign intervention.